Bovine Leptospirosis in Caatinga Biome, Brazil: New Insights into Diagnosis and Epidemiology - Barnabé, Nathanael Natércio da Costa; Soares, Rafael Rodrigues; Barros, Deivyson Kelvis Silva; Nogueira, Denise Batista; Costa, Flávia Teresa Ribeiro da; Araújo Júnior, João Pessoa [UNESP]; Malossi, Camila Dantas [UNESP]; Ullmann, Leila Sabrina [UNESP]; Costa, Diego Figueiredo da; Silva, Maria Luana Cristiny Rodrigues; Higino, Severino Silvano dos Santos; Santos, Carolina de Sousa Américo Batista; et al. (MDPI, 2023)
Bovine leptospirosis causes economic losses and raises public health concerns. It is possible that there are peculiarities in the epidemiology of leptospirosis in regions with a semiarid climate, such as the Caatinga biome in Brazil, where the climate is hot and dry, and the etiological agent require alternative routes of transmission. This study aimed to close knowledge gaps to the diagnosis and epidemiology of Leptospira spp. infection in cows from the Caatinga biome, Brazil. Samples of the blood, urinary tract (urine, bladder and kidney) and reproductive tract (vaginal fluid, uterus, uterine tube, ovary and placenta) were collected from 42 slaughtered cows. Diagnostic tests included were the microscopic agglutination test (MAT), polymerase chain reaction (PCR) and bacterial isolation. Anti-Leptospira spp. antibodies were found in 27 (64.3%) of the animals analyzed using MAT at a 1:50 dilution (cut-off 50), while 31 (73.8%) animals had at least one organ/fluid where the presence of Leptospira spp. DNA was identified, and 29 animals (69%) were positive at bacteriological culture. The highest sensitivity values for MAT were obtained at the cut-off point of 50. In conclusion, even under hot and dry climate conditions, it is possible that Leptospira spp. can spread through alternative routes such as venereal transmission; moreover, a cut-off of 50 is recommended for the serological diagnosis of cattle from the Caatinga biome.
Keywords: bacteriological culture; cut-off point; Leptospiraspp; PCR; semiarid conditions; serology